Ultrahigh-Gain Organic Electrochemical Transistor Chemosensors Based on Self-Curled Nanomembranes - Ferro, Letícia M. M.; Merces, Leandro; de Camargo, Davi H. S.; Bufon, Carlos C. B. [UNESP] (Wiley, 2021)
Organic electrochemical transistors (OECTs) are technologically relevant devices presenting high susceptibility to physical stimulus, chemical functionalization, and shape changes—jointly to versatility and low production costs. The OECT capability of liquid-gating addresses both electrochemical sensing and signal amplification within a single integrated device unit. However, given the organic semiconductor time-consuming doping process and their usual low field-effect mobility, OECTs are frequently considered low-end category devices. Toward high-performance OECTs, microtubular electrochemical devices based on strain-engineering are presented here by taking advantage of the exclusive shape features of self-curled nanomembranes. Such novel OECTs outperform the state-of-the-art organic liquid-gated transistors, reaching lower operating voltage, improved ion doping, and a signal amplification with a >104 intrinsic gain. The multipurpose OECT concept is validated with different electrolytes and distinct nanometer-thick molecular films, namely, phthalocyanine and thiophene derivatives. The OECTs are also applied as transducers to detect a biomarker related to neurological diseases, the neurotransmitter dopamine. The self-curled OECTs update the premises of electrochemical energy conversion in liquid-gated transistors, yielding a substantial performance improvement and new chemical sensing capabilities within picoliter sampling volumes.
Keywords: dopamine; doping; nanomembrane origami; organic electrochemical transistor; sensor